Relative price levels and current accounts: An exploration - Joshua Aizenman (University of California, Santa Cruz Institute for International Economics (SCIIE), 2008)
This paper studies the links between current accounts and relative price levels, finding that current account changes are associated with sizable future relative price levels effects. This is done in panel regressions of the Penn effect, adding a lagged current account/GDP and other explanatory variables. Higher GDP/capita and a greater export share of manufacturing tend to mitigate the real exchange rate impact of lagged current accounts. Active management of current accounts may provide a powerful adjustment channel, mitigating the real exchange rate effects of volatile terms of trade, and may explain the growing proliferation of Sovereign Wealth Funds.
Keywords: F15; F21; F32; 330; current account; relative price levels; real exchange rate; Sovereign Wealth Funds; Leistungsbilanz; Preisniveau; Kaufkraftparität; Zahlungsbilanzmechanismus; Theorie